Mixing instabilities during shearing of metals - Mohsen Pouryazdan; Boris J. P. Kaus; Alexander Rack; Alexey Ershov; Horst Hahn (Nature Communications, 2017)
The mechanisms behind deformation of multiphase solids are elusive. Here, the authors use X-rays and simulations to show that the same mechanisms causing rocks to fold occur at the micrometer scale in dual-metal lamellas of Ag/Cu and Al/Cu under high-pressure torsion, leading to vortices formation.